Ekspansi Bahan Ajar Sport Massage Berbasis Sony Vegas Dengan Versi Anchored Instruction Meluaskan Animo Belajar Mahasiswa - Ratno Susanto; Achmad Afandi; Nur Khozanah Ilmah (Jurnal Multidisiplin Madani, 2022)
Exploration of the scheme before preparing teaching materials for basic techniques, tactics, and strategies for Sony Vegas-based sports massage with an appropriate and effective version of the anchored study before expanding interest and learning development for students of the Physical Education and Recreational Health Study Program of IKIP Budi Utomo. The exploratory version of the expansion backs up the Research and Development (R&D) method with the 4D version (Define, Design, Develop, and Disseminate). The selection of this expansion version is based on the following: 1) there are revisions (evaluations) that are carried out continuously during the stages that are passed so as to realize better teaching materials, 2) this version is straightforward, but the implementation is systematic. The data collection techniques applied before processing and interpreting the development of reviews and product trials of expansion of teaching materials are quantitative and qualitative analysis techniques. As well as generating student learning motivation, especially taking part in sports massage courses, ahead of making good learning developments in the new era of average